Pengaruh Dewan Komisaris Independen, Komite Audit, Kompetisi dan Konservatisme Terhadap Manajemen Laba Pada Industri Perbankan Indonesia - Jane Rinelke Tinangon; Agung Nurmansyah; Anggit Dyah Kusumastuti (JURNAL EKONOMI BISNIS DAN KEWIRAUSAHAAN, 2021)
The aims of this study is to test the effect of the independent board of commissioners, audit committee, competition and conservatism towards earnings management in the Indonesian banking industry. Independent variables cover independentboard of commissioners, audit committee, competition, and conservatism. Whereas,dependent variable is earnings management assessing with discreationary accruals. The data of this research is secondary data from financial statements of companies listed on the Indonesia Stock Exchange in 2013-2017. The population was banking companies in Indonesia that were listed on the Indonesia Stock Exchange (IDX) in 2013-2017. Sampling technique used purposive sampling with 17 banking companies. Whereas,methods of data analysis used multiple linear regression test.The result show that the independent board of commissioners has a positive effect while the conservatism has a negative effect on earnings management. Futhermore, the audit committee and competition have no effect on earnings management. Simultaneously the four variables have a positive and significant effet on earnings management.